Answer this question now asap please show your solutions step by step and I'll make you brainliest only ifbyou have your solutions step by step
Pleasee question 36
Attachments:
![](https://hi-static.z-dn.net/files/dc8/dd2c0bfdf56d388d1fa4c96571897433.jpg)
Answers
Answered by
0
Answer:
-(-3)^3
= -((-3)^3)
= -(-27)
= 27.
HOPE IT HELPS
PLS MARK IT AS THE BRAINLIEST
AND DO FOLLOW ME
Answered by
1
Step-by-step explanation:
-(-3)^3=-(-3*-3*-3)=-(-27)=27
because - * - = +
+ * - = -
Similar questions
Social Sciences,
6 months ago
Science,
6 months ago
Physics,
1 year ago
Math,
1 year ago
Science,
1 year ago
World Languages,
1 year ago
Science,
1 year ago